2004
DOI: 10.1258/0956462042395104
|View full text |Cite
|
Sign up to set email alerts
|

Oral Kaposi's sarcoma in a non-HIV homosexual White male

Abstract: This paper reports the exceedingly rare occurrence of oral Kaposi's sarcoma in a non-HIV Caucasian White male. The lesion presented as a 8 mm vascular nodule on the buccal mucosa on the left. He was homosexual. The lesion was removed and histological examination confirmed Kaposi's sarcoma. The patient has been tested on 10 occasions for HIV from December 1998 to March 2004 and has been negative. The patient remains alive and well with no evidence of recurrence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 4 publications
1
22
0
Order By: Relevance
“…In another study, 17 Taiwanese patients were reported to have classic KS with lesions in the lower extremities but no immunodeficiency status [5]. KS in HIV‐negative homosexual men has also been described [6,7], and in a retrospective study of 28 men with HIV‐negative KS, the prognosis was good [7]. However, a few cases in HIV‐negative patients manifested as disseminated KS [8–10].…”
Section: Discussionmentioning
confidence: 99%
“…In another study, 17 Taiwanese patients were reported to have classic KS with lesions in the lower extremities but no immunodeficiency status [5]. KS in HIV‐negative homosexual men has also been described [6,7], and in a retrospective study of 28 men with HIV‐negative KS, the prognosis was good [7]. However, a few cases in HIV‐negative patients manifested as disseminated KS [8–10].…”
Section: Discussionmentioning
confidence: 99%
“…Its clinical presentation resembles classic KS, with cutaneous involvement, which most commonly occur on the lower limbs but also arms, genitals, and trunk. KS in the HIV‐negative MSM population runs an indolent course similar to classic KS; it is usually chronic, persisting over many years, and presenting as nodules or plaques on the lower extremities . This recently recognized subtype has been termed “nonepidemic KS.”…”
Section: Nonepidemic Ksmentioning
confidence: 99%
“…Three of the patients had KS lesions limited to the legs only, and two patients presented with a single KS lesion on the penis . In 2004, Kua et al reported the case of a 53‐year‐old homosexual man with KS of the buccal mucosa . The patient was observed over a 6‐year period without evidence of HIV, and no other cause of immunodeficiency was identified …”
Section: Nonepidemic Ksmentioning
confidence: 99%
See 1 more Smart Citation
“…186 Recrudescent or new KS after HAART may be a sign of IRIS, as may a flare of cutaneous and/or visceral KS. 16 Conjunctival, oral, 187,188 and genital KS can be striking (Figs 11 and 12). Although primary penile KS is uncommon in HIV-negative men, one should consider this possibility when treating nonspecific penile lesions.…”
Section: Clinical Featuresmentioning
confidence: 99%